Galectin-3 Binding Protein, Depression, and Younger Age Were Independently Associated With Alexithymia in Adult Patients With Type 1 Diabetes - Melin, Eva O.; Svensson, Ralph; Dereke, Jonatan; Hillman, Magnus (Frontiers in Psychiatry, 2021)
Aims: Alexithymia has been linked to cardiovascular disease. The aim was to explore whether the immuno-inflammatory variables galectin-3 binding protein (Gal3BP), sCD163 and galectin-3 were independently associated with alexithymia, while controlled for known risk factors for cardiovascular disease, such as depression, anxiety, impaired glycemic control, obesity, smoking and physical inactivity in patients with type 1 diabetes (T1D). Methods: Cross-sectional design. The participants were consecutively recruited from one diabetes out-patient clinic. Alexithymia, depression and anxiety were assessed by self-report instruments. Blood samples, anthropometrics and blood pressure were collected, supplemented with data from electronic health records. High Gal3BP was defined as ≥3.3 µg/ml, high sCD163 as ≥0.6 µg/ml, high galectin-3 as ≥2.6 ng/ml, impaired glycemic control as HbA1c >70 mmol/mol (>8.6%) and abdominal obesity as waist circumference ≥ 1.02 meters for men and ≥ 0.88 meters for women. Results: 292 patients participated (men 56%, age18-59 years, alexithymia prevalence 15%). Patients with alexithymia had higher prevalence of depression (34% vs 6%, p <0.001), anxiety (61% vs 30%, p <0.001), high Gal3BP levels (39% vs 17%, p = 0.004), high HbA1c levels (46% vs 24%, p = 0.006), and abdominal obesity (29% vs 15%, p = 0.045). Depression (adjusted odds ratio (AOR) 6.5, p < 0.001), high Gal3BP levels (AOR 2.4, p = 0.035) and age (AOR 0.96, p = 0.027) were independently associated with alexithymia. Abdominal obesity (AOR 4.0, p < 0.001), high Gal3BP levels (AOR 2.8, p = 0.002), and depression (AOR 2.9, p = 0.014) were associated with high HbA1c. Abdominal obesity and anxiety were associated (Crude odds ratio (COR) 2.4, p = 0.006). Conclusions: T1D patients with alexithymia had higher prevalence of high Gal3BP levels, depression, impaired glycemic control, anxiety, and abdominal obesity, which all are risk factors for cardiovascular disease. Only Gal3BP, depression and younger age were independently associated with alexithymia in adult patients with T1D.